Beyond Boundaries: The Relevance of R&D Innovation, Financial Ratios, and Revenue Diversification in Driving Business Growth in Technology Firms - Kadir, Eka Yuli; Eltivia, Nurafni; Riwajanti, Nur Indah (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
The National Association of Securities Dealers Automated Quotations Stock Market (NASDAQ) is the world's largest stock market, a significant source of investment in technology companies. Research and development (R&D) is one of the most critical components of the NASDAQ's growth strategy. The purpose of this research is to examine how R&D investment affects business growth, discuss how it relates to critical financial ratios like Return on Equity (ROE) and Return on Assets (ROA), and evaluate the revenue diversification tactics used by NASDAQ-listed technology companies 2018-2022. The results show that ROA positively influences revenue growth, which impacts business growth. However, ROE has no partial effects on business growth, and only one independent variable, the ROA variable, partially affects revenue growth. Therefore, this research is anticipated to provide useful advice on successfully combining innovation and financial stability to support long-term corporate growth and surpass preconceived notions for both businesses and academics. Research on growth strategy and corporate management in the rapidly advancing technological era could benefit significantly from this research.